Kissinger's Shadow : The Long Reach of America's Most Controversial Statesman - Grandin, Greg (New York Picador, 2016)
A new account of America's most controversial diplomat that moves beyond praise or condemnation to reveal Kissinger as the architect of America's current imperial stance.
Include Notes and Index.
The Long Reach of America's Most Controversial Statesman.
Keywords: Military policy -- Military policy--Decision making -- United States -- Diplomatic relations